On the Measurement of the Overall Degree of Income Stratification between Groups. (25th January 2017) - Allanson, Paul
Abstract : This paper proposes a new class of indices that measure overall stratification between groups in a population and can be decomposed as population‐weighted averages of pairwise indices. The indices capture not only the extent to which groups form well‐defined strata in the income distribution but also the scale of the resultant differences in equally distributed equivalent incomes between them, where these two factors play the same role as identification and alienation respectively in the measurement of polarization. The properties of the class as a whole are investigated as well as those of selected members of it: zeroth and first power indices may be interpreted as measuring the overall incidence and depth of stratification respectively, while second and higher power indices members are directly sensitive to the severity of stratification between groups. An illustrative application provides an empirical analysis of global income stratification by regions in 1993.